Comparison of body composition and functional profile of female basketball players - Causevic, D. (Homosporticus, 2016)
In many countries, basketball has established itself as one of the most popular sports. The aim of this study was to examine and analyze body composition and functional profile of cadet basketball players. The sample subjects were 20 female basketball players of KK Zeljeznicar (age = 15:30 ± 0.82; height = 172.0 ± 5.94), whose composition of the body (height, weight, BMI, FatP) and parameters of spirometry (FVC, FEV 1, FEV / FCV, PEF) were examined. The results showed that basketball players from KK Zeljeznicar are lower than their peers but they are much heavier and that the percentage of fat is a lot higher than in previous studies. Also all variables of spirometry indicate significantly lower means in relation to previous studies. These results indicate importance of further work on the physical preparation of a basketball player, because creation of adequate base directly affects better sports results.